2021
DOI: 10.18805/lr-592
|View full text |Cite
|
Sign up to set email alerts
|

Humidity Restriction, High Night Temperature and their Combination, during Post Flowering on Common Bean (Phaseolus vulgaris L.) Canopy and Pod Senescence

Abstract: Background: Common bean (Phaseolus vulgaris L.) grain filling is vulnerable to drought and heat stress. The objective of the study was to evaluate the effect of humidity restriction, high night temperatures and their combination in common bean.Methods: The plants were grown in pots at maximum field capacity (100% FC) until the grain filling began. Afterwards, maintained until harvest at: 1) 100% FC, 2) 50% FC at ambient day/night temperature (AT), 22.58°C/16.94°C, 3) 100% FC with high night temperature (HNT) 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…In this regard, Cayetano‐Marcial et al. (2021) documented differences in leaf and pod senescence between Rosa Bufa and OTI cultivars due to the combined effect of these factors. Furthermore, in relation to pleiotropy, the trade‐off between biomass and reproduction may be evident in subtler ways, such as the accumulation of nutrients in the seeds (Cortés et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, Cayetano‐Marcial et al. (2021) documented differences in leaf and pod senescence between Rosa Bufa and OTI cultivars due to the combined effect of these factors. Furthermore, in relation to pleiotropy, the trade‐off between biomass and reproduction may be evident in subtler ways, such as the accumulation of nutrients in the seeds (Cortés et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Given that elucidating the key points in the regulation of the synthesis and distribution of photoassimilates can contribute to designing drought‐tolerant genotypes (Montero‐Tavera et al., 2008), the present study hypothesized that the level of the water deficit (moderate and severe) differentially alters the distribution and accumulation of photoasmilates throughout the plant. Given that OTI variety shows asynchronous senescence between foliage and pods due to soil moisture deficiency (Cayetano‐Marcial et al., 2021), the objective of this study was to evaluate modifications in the 14 CO 2 assimilation capacity and biomass distribution in response to moderate and severe humidity restriction in common bean plants var. OTI at plant R8 stage.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, various studies have recognized the green color permanence in plants, which is known as "Stay Green", an agronomic character [31]. In common bean, it has been demonstrated that the green color permanence in pods varies among cultivars [32]. To confirm whether pod greenness is related to cellular structural integrity, the anatomy was analyzed in cross-sections of long and small pods of the plants with and without water restriction (Figure 2B).…”
Section: Discussionmentioning
confidence: 99%
“…The resolution of the digital camera (Baster AG, Ahrensburg, Germany) was 1628 × 1236 pixels using light in the RGB (400-700 nm) visible spectrum with a pixel size of 4.4 µm × 4.4 µm. The plants were imaged and analyzed with LemnaGrid software, and each image was segmented into green (healthy), yellow (senescent), and brown (necrotic) colors related to the physiology and phenology of the tissues [32].…”
Section: Phenotyping Analysismentioning
confidence: 99%
“…Flowers per inflorescence and number of pods per plant are the most important characters influencing pod yield under current (Lyngdoh et al, 2017) and in elevated CO 2 conditions (Rao et al, 2015). Water stress post-flowering accelerated the leaf and pod senescence (Cayetano-Marcial et al, 2021). Additionally, water stress significantly lowered seed yield.…”
Section: Effect Of Irrigation and Temperature Regimes On Yieldmentioning
confidence: 99%